Implementation of Multicultural Education for Class B, Raudlatul Athfal Ar Rafif, Kalasan, Sleman, Yogyakarta, Indonesia - Munastiwi, Erni (International Journal of Engineering and Technology, 2018)
This research is a contribution to science that aims to examine the implementation of multicultural education for early childhood. The research method used qualitative approach. Data sources are students, teachers, principals, parents, school committee and community. Data collection techniques by means of observation, interviews and questionnaires, documents and audiovisual materials. Observation focused on the implementation of learning. Interviews were conducted by interviewing principals, teachers, students, parents, school committees and the community. Documentation is devoted to documents used by principals, teachers and students to enliven the value of multicultural education. Required documents are annual, semester, weekly and daily programes, assessment document and others, media and supporting activities as well. Audiovisual materials is focused on learning recording. Interactive model data analysis techniques as well as their implementation take place continuously. Test data credibility using technique triangulation. The result of the research is the implementation of multicultural education implemented in Raudlatul Athfal (RA) Ar Rafif follows: First is designing through learning plan according to the development of multicultural education and the standard of achievement level of child development. Second is to implement planning-based learning process. Third, is conducting a learning assessment to measure the achievement of learning objectives. Fourth is inhibiting the factor of multicultural educational implementation. Fifth is supporting factor of multicultural educational implementation.Â Â